The Effect of Modern Tax Administration System, Taxpayer Satisfaction, Enforcement of Tax Sanctions and Distributive Justice on Taxpayer Compliance (Study On Taxpayers of Personal Persons Registered at The Holy Tax Service Office) - Setiarini, Sri Indah (Lembaga Riset Mutiara Akbar (LARISMA), 2022)
This study aims to examine the effect of modern tax administration system, taxpayer satisfaction, tax penalty enforcement, and distributive justice on taxpayer compliance. The population in this study is an individual taxpayer registered at KPP Pratama Kudus. The method used is purposive sampling with a total of 400 respondents. The analytical technique used is multiple linear regression analysis. The results of this study show that modern tax administration system, taxpayer satisfaction, and tax penalty enforcment have a positive effect on tax compliance, meanwhile, distributive justice have no effect on tax compliance